Cluster Life Cycle: A Study in the Vale dos Sinos Footwear Cluster - Schmidt, Vitor; Zen, Aurora Carneiro; Bittencourt, Bruno Anicet; Machado, Raquel Engelman (Revista de Negócios, 2020)
This research aims at analyzing the relation between the flow of knowledge, lock-in and stage of the lifecycle of a cluster. For that, the Footwear Cluster of Vale dos Sinos-Paranhana in Rio Grande do Sul was chosen as a study object. The results point out that the cluster is little collaborative and little innovative. The cluster is still recognized as a great footwear producer, but the own identity of the people with the cluster is being lost. The local culture does not promote the diffusion of knowledge, since the companies are closed. This research contributes with the comprehension of how the clusters develop, for this purpose, the flow of knowledge will have a central role in the renewal of the cluster. As a practical implication, the awareness of the difficulties and the necessary mechanisms to renovate a cluster are important so that it is possible to work on sectoral policies and of cluster. As theoretical contribution, the study reinforces that the lack of new knowledge influences the imprisonment, resulting from its dependent trajectory, leading it to the decline.